Impact of Extreme Droughts on Fish Assemblages in a Large South American Floodplain River - Espinola, Luis Alberto; Simōes, Nadson Ressyé; Rabuffetti, Ana Pía; Contreras, Félix Ignacio; Saucedo, Griselda Isabel; Abrial, Elie; Garelo, Nicolás; Stachiotti, Leonardo; Baigun, Claudio Rafael M.; Blettler, Martín César María; Dos Santos, Luciano Neves (Wiley, 2025)
Increasing anthropogenic pressures and climate change have significantly altered the hydrological dynamics of freshwater ecosystems, particularly in Latin America. The Paraná River in the La Plata Basin has experienced prolonged droughts, leading to reduced hydrological connectivity and habitat loss, which have severely impacted fish assemblages and reproduction of several species. This study analysed changes in fish assemblage structure during a prolonged hydrological drought (2021–2022) compared with regular hydrological pulse periods (2010 and 2016) in the middle Paraná River floodplain. The results show that prolonged droughts have disrupted typical temporal dynamics, restructured the fish assemblage and particularly affected the abundance and dominance of large migratory species, which account for many key ecosystem services and are the major target of local fisheries, with only sedentary and short-distance migratory species remaining dominant. Because climate models predict more frequent and severe droughts in the future, our study shows that prolonged hydrological droughts are transforming river-floodplain systems by reducing the frequency and intensity of pulse and flow pulses. This decline in hydrological variability leads to a reduced availability and diversity of habitats for fish nurseries, negatively impacting reproductive success and even affecting migratory signals essential for reproduction. As a result, species abundance and community composition are being significantly reshaped. An ecohydrological approach is recommended for sustainable water management, integrating adaptive strategies to mitigate the impacts of abnormal hydrological events, monitor ichthyofauna and maintain ecosystem services such as fisheries.